Value for Money dalam Kerjasama Pemerintah dan Badan Usaha Unsolicited pada Rumah Sakit Umum Daerah di Indonesia: Studi Kasus RSUD X - Fandi Galang Wicaksana; Rochmat Aldy Purnomo; Rischa Inung Fauziah; Desiana Rachmawati; Fabio Bolanda Sandy (JURNAL ILMIAH EDUNOMIKA, 2026)
Health infrastructure reforms in Indonesia and the rising burden of non-communicable diseases have intensified pressure on regional public hospitals to expand service capacity while maintaining fiscal sustainability. In response, unsolicited Public–Private Partnerships (PPPs) have emerged as an alternative procurement and governance mechanism for hospital infrastructure development. Despite their growing adoption, empirical evidence on whether unsolicited PPPs deliver Value for Money (VfM) remains limited, particularly in developing countries and the healthcare sector. This study examines the implementation of an unsolicited PPP at Regional General Hospital X in East Java, Indonesia, using an embedded mixed-methods case study design. Data were obtained from feasibility studies, government reports, institutional evaluations, performance documents, and semi-structured interviews. The analysis integrates the three dimensions of VfM in economy, efficiency, and effectiveness (3E) with Public Sector Comparator (PSC) analysis to assess the relative performance of PPPs compared with conventional public procurement. The findings indicate that unsolicited PPPs provide stronger projected service capacity, lifecycle efficiency, and public value than conventional schemes, with projected fiscal savings exceeding IDR 46 trillion under conservative recovery assumptions. Cardiology services demonstrated the highest efficiency and effectiveness performance, while oncology and stroke services remained constrained by higher treatment complexity and costs. However, the economic dimension could not be fully quantified due to limited expenditure realization data. The study further demonstrates that VfM in healthcare PPPs is shaped not only by financial efficiency, but also by governance quality, contract design, accountability mechanisms, and the alignment between private incentives and public objectives. This study contributes to the public sector accounting and governance literature by positioning VfM as a governance-based accountability framework for evaluating long-term public value creation in healthcare infrastructure partnerships.